"I Don't Know What I'm Doing… I Hope I'm Not Just an Idiot": The Need to Train Pediatric Urologists to Discuss Sexual and Reproductive Health Care With Young Women With Spina Bifida. Issue 10 (5th September 2018) - Streur, Courtney S.; Schafer, Christine L.; Garcia, Valerie P.; Wittmann, Daniela A.
Abstract: Introduction: Although pediatric urologists have taken responsibility for initiating discussions on sexual and reproductive health with spina bifida patients, research shows that very few girls and women with spina bifida have ever discussed this topic with any physician. Aim: We sought to better understand pediatric urologists' gaps in knowledge and training needs in the sexual and reproductive health education of women with spina bifida with the goal of creating a tool kit to equip providers to have these discussions. Methods: In this qualitative study, pediatric urologists were interviewed separately about their current practices, perceived barriers, knowledge gaps, and recommendations for the tool kit until thematic saturation was reached. The interviews were recorded and transcribed verbatim, then analyzed using grounded theory by 3 independent reviewers. Main Outcome Measures: To evaluate the perspectives and practices of pediatric urologists, we identified the overlapping themes of the interviews. Consensus on themes was reached. Results: 10 Pediatric urologists participated in the study, including 5 men and 5 women, of whom 4 were fellows and 6 were attending physicians (mean years of practice 18, range 6–31 years). The mean number of patients followed up in the respective spina bifida clinics or by the provider was 434 (range 24–1, 500). The following themes regarding pediatric urologists' experience providing sexual and reproductive health education to women with spina bifida emerged. Pediatric urologists': (i) lack of formal training; (ii) knowledge gaps such as spina bifida sexuality, fertility, and pregnancy experience; (iii) barriers to having sexual and reproductive health conversations such as lack of comfort and lack of time; (iv) facilitators of these conversations such as a long-term relationship with the patient and the patient's own initiative; (v) desire to learn and provide competent care; and (vi) recommendations for a web-based tool kit that would include content to address the knowledge gaps and training about how to start sexual and reproductive health conversations. Clinical Implications: These findings can provide the beginning concepts for the development of training on providing sexual and reproductive health education for pediatric urologists' care for women with spina bifida. Strengths & Limitations: This study gives the perspectives of 10 pediatric urologists with a diversity of backgrounds, but all of whom care for a large number of spina bifida patients. This does not give the perspectives of the spina bifida women themselves, which will be evaluated in the next phase of the study. Conclusion: Pediatric urologists are not trained and do not feel prepared to provide sexual and reproductive health education for girls and women with spina bifida. However, they do see it as their scope of practice and wish to acquire competence in this area.